Investigating the ME/CFS experience through qualitative analysis of memorial entries - Zoe Sirotiak; Hailey J. Amro (PLoS ONE, 2026)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is an impairing chronic condition characterized by exhaustion and worsening symptoms following exertion, often accompanied by pain, sleep issues, and cognitive issues. Historically, ME/CFS was not considered to be linked to mortality, however, more recent studies have questioned this assumption. The National Chronic Fatigue and Immune Dysfunction Syndrome (CFIDS) Foundation maintains a memorial list consisting of deceased individuals who had ME/CFS. This secondary qualitative thematic analysis analyzed 505 entries on the National CFIDS Foundation memorial list, inductively developing a codebook from the publicly available memorial records. Two coders independently coded each entry before meeting to develop themes that incorporated the understanding of each coder. Themes emerged within four societal levels: systemic neglect and institutional failure; clinical neglect and failures; social disconnection and advocacy; and personal burden and quality of life. Describing systemic neglect and institutional failure, entries recounted a lack of acknowledgement by health, insurance, and disability authorities, as well as a lack of investment in research and treatment of ME/CFS at the federal level. Negative healthcare experiences included misdiagnosis and misattribution of symptoms, dismissal, inadequate knowledge and experience with treating ME/CFS, and the recommendation of unhelpful treatments. The disbelief and misattribution by acquaintances described in the entries contributed to feelings of social isolation, leading some to turn to advocacy work and support groups. Entries also described the individual impact of the condition, including functional impairments, the impact of symptoms, management strategies, financial stress, and mental health symptoms. Some deaths were directly and indirectly attributed to ME/CFS by individuals with ME/CFS and their acquaintances. This analysis provides a glimpse of the lived experience as well as death of individuals with ME/CFS through the lens of acquaintances of the deceased, emphasizing the substantial impact of the condition.